Perspectives on evidence laundering in awarded collaboration agreements: a proposal on controlling prosecutorial malfeasance - Guilherme Brenner Lucchesi; Lucas Gandolfi Vida (Revista Brasileira de Direito Processual Penal, 2021)
This article identifies a possibility of dissimulation or concealment of the origin of unusable information in criminal proceedings as a source of evidence, in order to give an appearance of legitimacy to its origin, especially in awarded collaboration agreements. This phenomenon is dubbed “evidence laundering” by the authors and is of yet a procedural situation that is still insufficiently discussed in legal scholarship. To analyze this phenomenon, this article begins by examining the legal nature of awarded collaboration agreements, as well as the steps of their procedure. By analyzing evidence laundering from a perspective of preserving the chain of custody of evidence, the aim is to identify the legal consequences of this phenomenon. Based on the experience of CADE’s leniency program, possible measures to control this malfeasance by the prosecution are proposed. In conclusion, the article raises the possibility of establishing a single awarded collaboration center, combined with the dissemination of good practices in negotiating deals, as means to improve the evidence arising from these agreements, bringing greater legal certainty to would-be collaborators and avoiding evidence laundering.